2021
DOI: 10.1159/000518098
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Associated with Antidepressant Treatment on Major Depression

Abstract: Major depressive disorder (MDD) is a complex and multifactorial psychiatric disorder that causes serious health, social, and economic concerns worldwide. The main treatment of the symptoms is through antidepressant (AD) drugs. However, not all patients respond properly to these drugs. Omic sciences are widely used to analyze not only biomarkers for the AD response but also their molecular mechanism. In this review, we aimed to focus on omics data to better understand the molecular mechanisms involving AD effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that Mapk1 -encoded protein expression is increased in the PFC in the Flinders sensitive line (FSL), a genetic rat model of depression 64 . Moreover, CACNA2D1 , which has been detected in human genome-wide association data as a candidate gene for depression 65 and bipolar disorder 66 , has been suggested to be a potential target for depression treatment and rapid antidepressant effects 67 . However, further research should be performed to address this potential.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Mapk1 -encoded protein expression is increased in the PFC in the Flinders sensitive line (FSL), a genetic rat model of depression 64 . Moreover, CACNA2D1 , which has been detected in human genome-wide association data as a candidate gene for depression 65 and bipolar disorder 66 , has been suggested to be a potential target for depression treatment and rapid antidepressant effects 67 . However, further research should be performed to address this potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been described that through this mechanism of action, endogenous opioid peptides that are involved in antidepressant functions may be released [ 74 ]. Furthermore, genetic studies have identified genes such as IRAK3 and NME7 that could influence esketamine’s efficacy, suggesting their involvement in processes related to immune response, stress regulation, and neuronal connectivity [ 75 , 76 ]. In addition to improving depressive symptoms, esketamine treatment has also shown improvements in other aspects of mental health, such as insomnia, and is not associated with weight gain [ 77 ], making it especially attractive for certain patients.…”
Section: Treatment Options For Treatment-resistant Depressionmentioning
confidence: 99%
“…These factors can discourage patients from taking antidepressants regularly or even lead to their discontinuation, significantly reducing the chance of remission and triggering several complications including suicide [ 14 ]. A better understanding of the molecular mechanisms underlying DDs, including MDD and bipolar disorder (BD), seems to be necessary to obtain new, more effective drugs (both antidepressant and anxiolytic profile) [ 3 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%